Studies of Teaching and Learning English-Speaking Skills: A Review and Bibliometric Analysis - Wang, Juan; Abdullah, Rohaya; Leong, Lai-Mei (Frontiers in Education, 2022)
This study conducted a comprehensive historical review and bibliometric analysis of the English-speaking (ES) education literature and mapped out the current state of the field, trends, and emerging topics, as well as identifying gaps where further research is needed. It retrieved 361 sample documents on ES teaching and learning in Scopus (2010–2021) under certain conditions and analyzed the data extracted using Excel and VOSviewer 1.6.17 from the perspectives of the number of yearly publications, countries, authors, citation numbers, and keywords. The findings show that the number of publications on ES education increased from 2010 to 2021 but that there was a lack of sustained engagement with this topic from researchers. Countries with an ESL or EFL context focused more on the subject of ES, although studies from native ES countries were more influential. The research topics showed a multidimensional trend, covering communicative skills, language knowledge, assessment, teaching or learning methods, ICT-related applications, and cognitive factors, of which ICT-related applications (such as flipped classrooms, blended learning, e-learning, etc.) and cognitive factors (such as motivation, anxiety, affect, etc.) were the areas of focus. Students at higher institutions, rather than children, became the main research subject of ES education over the period studied.